The Role of Wearable Technology in Monitoring Children’s Health and Fitness - Yusuf Hasan Karim; Omar Khalid Zubair (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
Wearable technology has become increasingly popular in healthcare for monitoring personal health metrics. This paper explores how wearable devices are being utilized to track children's health and fitness levels. The study focuses on devices that monitor heart rate, physical activity, sleep patterns, and nutrition, assessing their impact on improving children's health outcomes. The paper concludes that wearable technology can play a significant role in promoting healthy lifestyles among children and preventing chronic health issues.